2004
DOI: 10.1080/10606820490464343
|View full text |Cite
|
Sign up to set email alerts
|

Proteinous Amino Acids in Muscle Cytosol of Rats' Heart, After Their Treatment with Propranolol, Pentylenetetrazol or Reserpine

Abstract: Tissue levels of nineteen amino acids and total free amino acids, were assayed by gas-liquid chromatography in cytosols of rat atrial and ventricular muscle cardiomyocytes. The tissues were assayed after the rats had been administered IP with the three cardioactive drugs, exerting a significant effect on their heart action: propranolol, pentylenetetrazol and reserpine. It was demonstrated that while in the atrial and ventricular cardiac muscle cytosols of control rats, arginine, glutamine and cysteine were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It was demonstrated that both physical stress and the three drugs, affected the levels of proteinous amino acids, mostly cysteine, arginine, histidine, isoleucine, alanine and tyrosine (Gabrys et al 2003(Gabrys et al , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that both physical stress and the three drugs, affected the levels of proteinous amino acids, mostly cysteine, arginine, histidine, isoleucine, alanine and tyrosine (Gabrys et al 2003(Gabrys et al , 2004.…”
Section: Introductionmentioning
confidence: 99%